1989
DOI: 10.1099/00221287-135-12-3209
|View full text |Cite
|
Sign up to set email alerts
|

Antigenic and Structural Analysis of Treponema denticola

Abstract: Polypeptide and Western immunoblot profiles of subcellular fractions of Treponema denticola ATCC 33520 have been determined by SDS-PAGE of Triton X-100-soluble and -insoluble fractions, a lipopolysaccharide-enriched fraction and purified flagella. Major Triton X-100-soluble polypeptides of 72, 68, 54 and 52 kDa were detected. The 54 kDa polypeptide appeared to be a breakdown product of a larger, heat-modifiable polypeptide. Based on the results of SDS-PAGE analysis and immunoblotting of proteinase K digests of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
2

Year Published

1991
1991
2010
2010

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(45 citation statements)
references
References 31 publications
(19 reference statements)
4
39
2
Order By: Relevance
“…PFs were com- prised of two major bands at 38 and 35 kDa and two minor bands at 32 and 29 kDa (42,43). These results are similar to those reported by Cockayne et al (9). Two-dimensional gel electrophoresis of whole-cell lysates (Fig.…”
Section: High-voltage Analysis Of Wild-type Cellssupporting
confidence: 82%
“…PFs were com- prised of two major bands at 38 and 35 kDa and two minor bands at 32 and 29 kDa (42,43). These results are similar to those reported by Cockayne et al (9). Two-dimensional gel electrophoresis of whole-cell lysates (Fig.…”
Section: High-voltage Analysis Of Wild-type Cellssupporting
confidence: 82%
“…MgCl 2 ) induced a separation in aggregable and nonaggregable moieties, which could have enhanced minor parts of very large and perhaps different lipid molecules (such as the enterobacterial common antigen present in Enterobacteriaceae). Others suggest that an LPS-like structure exists in a different strain of T. denticola (ATCC 33520) on account of their findings of proteinase-indigestible low molecular weight molecules in silverstained gels (36). An interesting observation in our study is the actual size of OML521, which is around the same size as RaLPS, a structure essential to the assembly of perfectly active porin-trimers in normal outer membranes (37).…”
Section: Resultssupporting
confidence: 59%
“…However, the mol. wt of 56-58 kDa for the OM protein reported here is different from that reported by Cockayne et al 42 and Cockayne et al 42 reported that four major OM polypeptides, of 73, 68, 54 and 52 kDa, were isolated from T. denticola ATCC 33520 by a Triton XlOO solubilisation procedure, whereas Yotis et al 43 reported that, for three strains of T. denticola, OM preparations extracted by SDS contained polypeptides of 66,53 and 45 kDa. Although the 53-kDa protein described by these authors may be a serovar-specific antigen, our results showed that the 5658-kDa protein was speciesspecific.…”
Section: Discussioncontrasting
confidence: 56%
“…However, without a comparative study involving all the isolation procedures used by the different groups, it is difficult to ascertain whether these proteins are truly one and the same. Cockayne et al 42 noted that the 54-kDa protein may be a breakdown product of a larger, heat-modifiable polypeptide. Other finding^^^.^^ suggest that the OM proteins may be involved in the binding of host serum proteins such as laminin, fibronectin and fibrinogen, or in the adherence to host tissues.…”
Section: Discussionmentioning
confidence: 99%